EVALUASI MUTU BERAS MERAH DAN BERAS HITAM LOKAL PADA LAHAN PERLADANGAN KABUPATEN BULUNGAN, KALIMANTAN UTARA: Evaluation Of Red Rice Quality And Local Black Rice On Land Breaking, Bulungan District, Kalimantan Utara - Fitrah Pangerang; Nila Rusyanti (Hasanuddin University Food Science and Technology Study Program, 2019)
Bulungan Regency is one of the contributors to the production of local rice commodities in North Kalimantan. This study aims to identify the characteristics and quality of local brown rice and black rice traditionally cultivated on farms. This research was conducted by exploratory methods. The amount of rice taken is 1 kg. Each brown rice and local black rice were analyzed for physical properties and quality of rice according to SNI quality class 01-6128-2015. The results of the analysis of the physical properties of local brown rice are of medium and short size. Medium size, namely Tanjung.Tanjung Palas with size (6.3 mm), and BM. Teras Baru (6.0 mm), while the short size is BM. Clubers with sizes (5.0 mm), BM. Selimau (5.3 mm) and BM Pimping (5.0 mm). Whereas the local black rice has medium and short sized categories. Medium size namely BH. Selimau (6.3 mm) and BH. Tobulo (6.0 mm), while the short size is BH. Braid (5.0 mm). The form of local brown rice has a round and medium shape. Round shape on BM. Club and BM. Teras Baru, while the form of medium rice in BM.Selimau, BM. Tanjung Palas and BM. Pimping. Whereas black rice has a medium and slim shape. Medium form at BH.Pejalin and BH.Tobulo, slim form of rice at BH. Selimau. Judging from the quality of rice shows that local brown rice that meets quality standards, namely BM. Tanjung Palas with medium quality class 3. While black rice that meets quality standards is Pejalin black rice with medium quality class 3. While red rice and other local black rice do not meet quality standards. This shows that Bulungan local rice needs to be done better postharvest handling to improve the quality of rice so that the rice produced is able to compete in the market. Conclusion Local Bulungan rice has characteristics with varying size and shape of rice, namely round, slender medium with relatively low quality.